Social Security/Medicare (Tax Management Financial Planning Journal, 2007)
H.R. 3932 and S. 2219 the Medicare Prescription Drug Savings and Choice Act, would require the Department of Health and Health and Human Services to establish a Medicare-run drug plan as an alternative to privately offered Part D plans. The bill would require HHS to negotiate drug prices for individuals enrolled in the plan. On October 17, the maximum amount of earnings subject to Social Security tax will increase to $102,000 in 2008, up from $97,500 in 2007.